2013
DOI: 10.1103/physreva.88.012501
|View full text |Cite
|
Sign up to set email alerts
|

Radiative decay from doubly and singly excited states of He-like nickel

Abstract: Fully relativistic calculations on the level energies and radiative lifetimes for all the low-lying levels of He-like Ni have been systematically carried out and attention has been paid to provide a complete tabulation of data for all the conceivable one-and two-electron one-photon transitions from levels of 2p 2 configuration decaying sequentially to the 1 S 0 ground state. Large-scale multiconfiguration Dirac-Fock wave functions have been applied to study the level features. The accuracy of our computed data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The newly developed X-ray free-electron lasers (FEL) provide a unique opportunity to investigate the behavior of inner-shell vacancy ions (Young et al 2010;Bucksbaum et al 2011;Düsterer et al 2011;Kanter et al 2011;Meyer et al 2012). The theoretical studies of the K-vacancy doubly excited levels of heliumlike ions are mostly based on non-relativistic theory or confined to some selected transitions within 2l2l and 2l3l configurations , 1978, 1980Dubau et al 1981;Safronova & Senashenko 1977;Karim & Bhalla 1986;Mosnier et al 1986;Cornille et al 1990;Deng-Hong et al 2006;Karim 2010;Kadrekar & Natarajan 2011;Natarajan & Kadrekar 2013;Natarajan 2014). The most recent and complete of these studies has been reported by Goryayev et al (2006), who presented the wavelengths and radiative transition probabilities for transitions of 2l 2l − 1s2l and 2l 3l − 1s2l, 1s3l in ions with Z = 6−36 using the Z-expansion method.…”
Section: Introductionmentioning
confidence: 99%
“…The newly developed X-ray free-electron lasers (FEL) provide a unique opportunity to investigate the behavior of inner-shell vacancy ions (Young et al 2010;Bucksbaum et al 2011;Düsterer et al 2011;Kanter et al 2011;Meyer et al 2012). The theoretical studies of the K-vacancy doubly excited levels of heliumlike ions are mostly based on non-relativistic theory or confined to some selected transitions within 2l2l and 2l3l configurations , 1978, 1980Dubau et al 1981;Safronova & Senashenko 1977;Karim & Bhalla 1986;Mosnier et al 1986;Cornille et al 1990;Deng-Hong et al 2006;Karim 2010;Kadrekar & Natarajan 2011;Natarajan & Kadrekar 2013;Natarajan 2014). The most recent and complete of these studies has been reported by Goryayev et al (2006), who presented the wavelengths and radiative transition probabilities for transitions of 2l 2l − 1s2l and 2l 3l − 1s2l, 1s3l in ions with Z = 6−36 using the Z-expansion method.…”
Section: Introductionmentioning
confidence: 99%
“…While the former contribution is evaluated in the hydrogenlike approximation, the latter correction is treated perturbatively. The theoretical background using relativistic wave functions and higher-order corrections is described in detail in the literature [20][21][22][23][24]. The generation of nearly exact atomic state functions using systematic expansions of the orbitals in the active space has been discussed in our earlier studies [7,19,25].…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…An attempt has also been made to analyze the importance of the Breit interaction on these transitions. The calculations have been carried out using the GRASP2K code [20,21], which is a modification of the GRASP92 code [22]. As this type of transition is due exclusively to the correlated motion of the two electrons and hence very sensitive to the nature of the spin orbitals of the initial and final states, we have carried out two different versions of the optimal level scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The TEOP process was first predicted theoretically by Heisenberg in 1925 [21] and was observed by Wölfli et al in ion-atom collision experiments between Ni-Ni, Ni-Fe, Fe-Ni and Fe-Fe in 1975 [22]. Since then, TEOP transitions have been widely studied both theoretically and experimentally [23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many works related to the energy levels and transition properties of inner-shell hole states in the past several decades [25][26][27][28][29][30][31][32][33][34][35][36][37], but only a few studies have focused on He-like ions [28][29][30][31][32][33][34][35]. The He-like ion is a two-electron system with a simple structure and an electron correlation effect and is a good candidate with which to study the TEOP process.…”
Section: Introductionmentioning
confidence: 99%